Discovering interesting knowledge in databases – Data Mining with classification / Kheong Ling Ling - Kheong , Ling Ling (2003)
This project is prepared to fulfill the requirement of the Bachelor of Information Technology. The development of implementation of Data Mining is highlighted in this document. Data Mining as well as knowledge discovery is a solution to overcome data explosion problem. It is an automated data collection tools and mature database technology lead to tremendous amounts of data stored in database, data warehouses and other information repositories. The main purpose if this research is to find out the useful and power of data mining in the data management. In order to discover the usefulness of data mining, a system of sales-marketing anakysis tool had been set up. This can be used to analyze the data from the database and only the related data will be shown as the result. It means that we no need to face all the data by selecting the appropriate one manually. As a result, it can reduce resources and energy on works. The literature review in the chapter II is a part that gathered all the related system that similar or using Data Mining as well. In this chapter, it consists of the analysis efficient. Besides, the information about other systems would be a reference to this research as well. The Waterfall model with prototyping has been chosen as the software life-cycle model to develop the system. The development technologies and tools are Java, Microsoft Access in the platform of Microsoft Windows 2000. The report will fully focused on the introduction to the system, literature review, systems analysis and system design till evaluation of system.